91.8k views
1 vote
Solve for x.
3(-4x-1)-2x+4=43
Please help I’m crying my eyes out I hate delta math

1 Answer

0 votes

Answer:

x = - 3

Explanation:

3 (-4 x - 1) - 2 x + 4 = 43

Expand the terms in the bracket

That's

- 12x - 3 - 2x + 4 = 43

- 14x + 1 = 43

Using the subtraction property subtract 1 from each side of the equation

- 14x + 1 - 1 = 43 - 1

- 14x = 42

Divide both sides by - 14


( - 14x)/( - 14) = - (42)/(14)

We have the final answer as

x = - 3

Hope this helps you

User Wakeupbuddy
by
5.0k points